KEGEL EXERCISE SEBAGAI UPAYA MENURUNKAN TINGKAT INKONTINENSIA URINE PADA LANSIA - Putri, Oktavia Andika; Sudarsih, Sri (Jurnal EDUNursing, 2025)
One of the decline in body systems experienced by elderly is urinary system. In elderly, the decrease in the hormone estrogen causes atrophy of the urethral tissue and the effects of childbirth cause weakness of the pelvic floor muscles which can lead to disturbances in controllig urine output, which is called urinary incontinence. Elderly who experience urinary incontinence will increase the risk of falling because they have to go to the toilet many times, resulting in urinary tract infections and sepsis. The psychosocial aspect of the elderly will feel ashamed so they withdraw from society because they often urinate, resulting in low self-esteem, depression, and increased dependence on others. Efforts that can be made to improve urinary incontinence include non-pharmacological therapy in the form of Kegel exercises. The purpose of this study was to determine the effect of Kegel exercise on urinary incontinence in the elderly at Pesanggrahan PMKS Majapahit, Mojokerto Regency. The research design used preexperimental, the type of research used was one group pretest-posttest design. The number of samples is 24 elderly people with a sampling technique using purposive sampling. Data collection was carried out using a questionnaire. The statistical test of this study used the Wilcoxon sign rank. Based on the Wilcoxon test statistic, the difference between pretest and posttest was 7.92 with a p value of 0.000, which means that there is a significant effect of Kegel exercise on urinary incontinence in the elderly at Pesanggrahan PMKS Majapahit, Mojokerto Regency. It is hoped that the provision of Kegel exercises can be carried out routinely so that it can reduce the level of urinary incontinence. Keywords: Elderly, Kegel exercise, urinary incontinenc.